If x → 1 lim x − 1 x n + 2 x − 3 = 2 5 , what is the value of n ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
what happen if i told you that, you don't need use H'lopital rules for find the answer x − 1 x n − 1 + x − 1 2 x − 2 = x 1 + x 2 + x 3 + . . . + x n − 1 + 2 = 2 5
Log in to reply
Nice! I didn't see that, but that's a great solution!
I did the same thing. You are just finding the value of n that makes this statement true where x = 1 . 2 + i = 1 ∑ n x i = 2 5
You should add another 1 since x − 1 x n − 1 = 1 + x + ⋯ x n − 1 .
Ahh... I see my mistake, forgot the 2...
Differentiating the numerator and denominator (L'Hôpital's Rule), x → 1 lim x − 1 x n + 2 x − 3 = x → 1 lim 1 n x n − 1 + 2 Now, it is convenient to plug-in 1 to the limit. We are left with the following: n ⋅ 1 ( n − 1 ) + 2 = 2 5 ⇒ n + 2 = 2 5 ⇒ n = 2 3
*using l hospital method * and putting x=1 we get nx1+2=25 so n=23
by L' Hospitals rule we differentiate both numerator and denominator to get nx^(n-1)+2 and put x=1 to get n = 23
Use L'Hopital Rule. Differentiate both the numerator and denominator w.r.t. x
Let start this problem using L'Hôpital's rule
L'Hôpital's rule states that
lim x → c f ( x ) = lim x → c g ( x ) = 0 or ± ∞ and,
lim x → c g ′ ( x ) f ′ ( x ) exists and g ′ ( x ) = 0 for all x,
then lim x → c g ( x ) f ( x ) = lim x → c g ′ ( x ) f ′ ( x )
So let Differentiate Numerator and Denominator individually,
So we are left with lim x → 1 n x n − 1 + 2 = 2 5
Replacing x = 1 we get n + 2 = 2 5 ⟹ n = 2 3
THE MOST ELEGANT SOLUTION... GREAT WORK EULER!!!!
With L'Hospital ---> become {n.x^(n-1) + 2 }/ 1 = 25 ----> n*1 + 2 = 25 ---> n = 25 - 2 = 23. Answer : 23
If we replace x with 1 for every term involving x, we get an expression which looks like this: 1 − 1 1 n + 2 × 1 − 3 = 2 5
This leaves us with 0 in the denominator which doesn't work, so we must use L'Hopital's rule to answer this question. L'hopital's rule basically says that if we replace the expression in the numerator ( x n + 2 x − 3 ) with it's derivative function ( n x n − 1 + 2 ), and the expression in the denominator ( x − 1 ) with it's own derivative function ( 1 ), we will render the same limit value as we would had we evaluated the original expressions. Therefore we end up with this:
1 n x n − 1 + 2 = 2 5
which - as there is 1 in the denominator - can be written as:
n x n − 1 + 2 = 2 5
From here we can subtract two from both sides:
n x n − 1 = 2 3
Now we can solve n. We have been told that as x approaches 1 the limit tends to 23, so we can go straight ahead and see whether substituting 1 into x works. It does - 1 to the power of any natural number such as n is always equal to 1, and therefore n × 1 n − 1 = 2 3 will easily render a value for n. All we need to do now is divide 23 by one (rearrange to x n − 1 2 3 = n ) leaving us with the answer:
n = 2 3
Problem Loading...
Note Loading...
Set Loading...
Notice that 1 − 1 ( 1 ) n + 2 ( 1 ) − 3 = 0 0 . So we can simplify the top and bottom expression by L'Hopital's Rule; we differentiate both the numerator and the denominator. x → 1 lim x − 1 x n + 2 x − 3 = x → 1 lim 1 n x n − 1 + 2 = 2 + x → 1 lim n x n − 1 = 2 + n ( 1 ) n − 1 = 2 + n Thus, n + 2 = 2 5 , and n = 2 3 .